Quantitative comparison of a human cancer cell surface proteome between interphase and mitosis. (4th December 2014) - Özlü, Nurhan; Qureshi, Mohammad H; Toyoda, Yusuke; Renard, Bernhard Y; Mollaoglu, Gürkan; Özkan, Nazlı E; Bulbul, Selda; Poser, Ina; Timm, Wiebke; Hyman, Anthony A; Mitchison, Timothy J; Steen, Judith A
Abstract The cell surface is the cellular compartment responsible for communication with the environment. The interior of mammalian cells undergoes dramatic reorganization when cells enter mitosis. These changes are triggered by activation of the CDK1 kinase and have been studied extensively. In contrast, very little is known of the cell surface changes during cell division. We undertook a quantitative proteomic comparison of cell surface‐exposed proteins in human cancer cells that were tightly synchronized in mitosis or interphase. Six hundred and twenty‐eight surface and surface‐associated proteins in HeLa cells were identified; of these, 27 were significantly enriched at the cell surface in mitosis and 37 in interphase. Using imaging techniques, we confirmed the mitosis‐selective cell surface localization of protocadherin PCDH7, a member of a family with anti‐adhesive roles in embryos. We show that PCDH7 is required for development of full mitotic rounding pressure at the onset of mitosis. Our analysis provided basic information on how cell cycle progression affects the cell surface. It also provides potential pharmacodynamic biomarkers for anti‐mitotic cancer chemotherapy.